Sex-association experiments reveal the true identity of Physetopoda lampedusia (Invrea, 1957) (Hymenoptera, Mutillidae, Smicromyrmini) - Matias, Rafael (Zootaxa, 2023)
Arthropod biodiversity is still insufficiently known in large areas of Europe, such as the Iberian Peninsula, regarding several insect groups. Mutillid wasps (Mutillidae), markedly sexually dimorphic ectoparasitic species, are poorly known Hymenoptera, with a number of species awaiting formal description and others known only from one sex. Sexual associations have been historically difficult to establish for most mutillid wasp species; in an European context, the species in tribe Smicromyrmini, particularly in the genera Smicromyrme Thomson, 1870 and Physetopoda Schuster, 1949, have presented the biggest challenges. In this paper, the hitherto unknown male of Physetopoda lampedusia (Invrea, 1957) is recognized as Ephutomma montarcense ((Mercet MS.) Giner Marí, 1944), with the former name falling into synonymy. A total of 63 females identified as P. lampedusia and 35 males identified as E. montarcense were collected in Portugal from 1999–2022. The correct sex association was confirmed through pairing experiments in captivity and is supported by circumstantial field observations in situ. Redescriptions of both male and female, as well as behavioural notes, are presented. Ephutomma montarcense is new for Portugal and its distribution is thus extended to Lampedusa Island (Italy) and Morocco, where it had been recorded as P. lampedusia, with Ephutomma representing a new genus for these three countries. The reliability of the method used, as well as the generic position and authorship of the species are briefly discussed.